Adult education and community action : adult education and popular social movements - Lovett, Tom; Clarke, Chris; Kilmurray, Avila (Routledge, 2019)
Originally published in 1982, this book discusses the role of adult education in social and community action. In particular it presents a critical assessment of 'community education' and the theories of Illich, Freire and Gramsci and it proves that there is a radical adult education tradition in the USA, Europe and North America which can offer many insights into the contemporary debate about the role of adult learning. The material is based on a decade of practical involvement in community action and education in Great Britain and Northern Ireland, where - despite deep political and religious divisions - community action has united Catholics and Protestants in a common resolve.- Resumé vydavatel
"First published in 1983 by Croom Helm Ltd"--Title page verso
Keywords: vzdělávání dospělých -- sociální aspekty -- Velká Británie; komunitní práce -- Velká Británie; adult learning -- social aspects -- Great Britain; community work -- Great Britain; elektronické knihy; monografie; electronic books; monographs